Pelaksanaan Kampung Keluarga Berencana Di Kelurahan Langnga Kecamatan Mattiro Sompe Kabupaten Pinrang (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to describe and explain the implementation of the Family Planning Village in Langnga Village, Mattiro Sompe District, Pinrang Regency. The research used a qualitative descriptive method by conducting data collection techniques through observation and interviews. The results of this study showed that the standard and target aspects of the implementation of the KB village policy were quite good. This seen from the existence of the SOP in the form of a technical manual for the KB Village and the implementor's understanding of the standards and objectives of the policy itself. Communication aspects between organizations, communication to the community regarding the implementation had been running effectively, especially in terms of socialization, the characteristics of the executing agent, the bureaucratic structure of the division and authority and the character of the KB Village officers in its implementation was quite clear and good, it seen from  bureaucratic structure and its officers the characteristics of a good policy implementing agent. and the Social, Political and Economic Environment, the response of the community and all parties in the implementation of the KB Village could run well and maximally. The indicators were not going well and had shortcomings include resources and the disposition or attitude of the implementers.                                                       Keywords: Implementation, Family Planning Village